2016
DOI: 10.1007/s00723-016-0846-9
|View full text |Cite
|
Sign up to set email alerts
|

NMR Techniques in Metabolomic Studies: A Quick Overview on Examples of Utilization

Abstract: Metabolomics is a rapidly developing branch of science that concentrates on identifying biologically active molecules with potential biomarker properties. To define the best biomarkers for diseases, metabolomics uses both models (in vitro, animals) and human, as well as, various techniques such as mass spectroscopy, gas chromatography, liquid chromatography, infrared and UV–VIS spectroscopy and nuclear magnetic resonance. The last one takes advantage of the magnetic properties of certain nuclei, such as 1H, 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 72 publications
1
44
0
Order By: Relevance
“…Another exciting application of NMR spectroscopy is the analysis of semi-solid samples such as fresh plant leaf or intact tissues via the implementation of high resolution solid state magic angle spinning (HR-MAS) NMR [147]. In this technique, the sample is mixed with a minimal volume of solvent.…”
Section: Solid State Nmr Based Metabolomicsmentioning
confidence: 99%
“…Another exciting application of NMR spectroscopy is the analysis of semi-solid samples such as fresh plant leaf or intact tissues via the implementation of high resolution solid state magic angle spinning (HR-MAS) NMR [147]. In this technique, the sample is mixed with a minimal volume of solvent.…”
Section: Solid State Nmr Based Metabolomicsmentioning
confidence: 99%
“…Metabolomics is one of the newest 'omics' sciences that has been recently developed to determine novel biomarkers for multiple human diseases/disorders, and that could be used to understand the underlying mechanisms of cancer development (7). It has been reported that metabolome changes can reflect the pathophysiological status of biological systems, such as in ovarian and liver cancer (8).…”
Section: Introductionmentioning
confidence: 99%
“…The untargeted metabolomics is different from targeted method, which shows in these aspects, such as no hypothesis-driven strategy, and the whole comprehensive study variations of metabolome in a biological system without bias for exploration of metabolite biomarkers for impactful prediction, diagnosis, and prognostic assessment [80,96]. The current techniques used to qualify and quantify the metabolomic variations are nuclear magnetic resonance (NMR)-based methods and mass spectrometry (MS)-based methods [88,[100][101][102]. NMR-based methods involve one-dimensional NMR (1D-NMR), two-dimensional NMR (2D-NMR), and three-dimensional NMR (3D-NMR).…”
Section: Metabolomicsmentioning
confidence: 99%
“…NMR-based methods involve one-dimensional NMR (1D-NMR), two-dimensional NMR (2D-NMR), and three-dimensional NMR (3D-NMR). The way to provide chemical structural and molecular environment information is utilizing the interaction of spin active nuclei ( 13 C, 1 H, 31 P, 19 F) with electromagnetic fields [100,101]. NMR-based methods possess many advantages, including nondestruction of sample, minimal sample preparation, high reproducibility, relative high throughput, availability of databases, and availability of molecular dynamic and compartmental information with diffusional methods.…”
Section: Metabolomicsmentioning
confidence: 99%